FINANCIAL INSTRUMENTS: ACCOUNTING TREATMENT OF RELATED REVENUES AND COSTS (International Congress on Economics, Management and Business Studies, 2026)
In the context of ongoing globalization and the rapid development of financial markets, financial instruments are becoming increasingly important strategic components of economic entities’ activities. Through these instruments, enterprises are able to raise capital, expand investment opportunities, efficiently allocate financial resources, and manage various financial risks. This, in turn, contributes to ensuring economic stability and improving business performance efficiency.